Pengaruh Derajat Desentralisasi Fiskal terhadap Pertumbuhan Ekonomi di Wilayah Barat Selatan Provinsi Aceh Periode Tahun 2011-2019 - Alisman, Alisman; Sufriadi, Dedi (Lembaga KITA, 2020)
The purpose of this study was to determine the effect of the degree of fiscal decentralization on economic growth in the South West Region of Aceh Province for the period 2011-2019. The data used are secondary data obtained from the Provincial Statistics Agency (BPS) and districts/cities in the South West region of Aceh Province, as well as from related agencies that have relevance to the subject matter of this research. This study uses a simple linear regression analysis model. The variables used are economic growth (dependent variable) and fiscal decentralization (independent variable). The results showed that the degree of fiscal decentralization in the South West Aceh region had a positive effect on economic growth in the South West Aceh. It is hoped that the District / City Governments of the South West of Aceh Province can increase economic growth, and explore productive and potential economic sectors that can influence the degree of fiscal decentralization in the South West Region of Aceh Province.Â Keywords: Economic Growth, Fiscal Decentralization.